Implementation of Lean Technique to Improve Efficiency in Quail Egg Farming - Rafly Galih Saputra; Muhammad Ridwan Andi Purnomo (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
The quail farming industry in Indonesia has recently experienced significant growth, which has led to an increase in demand for quail eggs. This shows substantial challenges in quail egg farming, namely low operational efficiency and high levels of waste in the production process. This study aims to improve operational efficiency by reducing waste in a quail egg farming production at CV. Vigaza uses lean manufacturing and the theory of constraints. Lean tools such as value stream mapping, waste assessment model, and value stream analysis tools are applied to identify the dominant wastes. The theory of constraints is used to determine the root cause using the current reality tree. The process activity value-added ratio has improved from 60.73% to 68.91%, lead time has decreased from 12.1 to 10.99 days, and the defect rate has reduced from 0.68% to below 0.5%. Overproduction is recommended to align production with the market demand rather than the production cycle. Integrating the lean method and the constraint theory effectively reduced waste in a small-scale agricultural production, a quail egg farm. These findings suggest a potential for adopting lean techniques in the agricultural sector in Indonesia.